'Homeschooling in times of corona': exploring Mexican and German primary school students' and parents' chances and challenges during homeschooling. Issue 1 (1st January 2021) - Pozas, Marcela; Letzel, Verena; Schneider, Christoph
ABSTRACT: The Corona virus (COVID-19) crisis forced many countries to follow strict protocols ordering schools to close. With schools under lockdown, homeschooling has become the only form of schooling available. Reports have indicated that parents and students have struggled with the challenges of homeschooling. Against this background, this study explored primary school students and parents' educational chances and challenges during homeschooling in two countries: Mexico and Germany. Comparing these two countries can shed light into potential differences of how inclusive approaches have been incorporated in homeschooling. Following a qualitative approach, thirteen semi-structured interviews were conducted with parents and school students. Results from a qualitative content analysis revealed that parents across both countries face challenges to organise homeschooling and motivate their children. However, they spent more time with their children. Primary school students in Germany and Mexico are challenged considerably by the loss of social contact.